2021
DOI: 10.1016/j.jtho.2021.01.323
|View full text |Cite
|
Sign up to set email alerts
|

PS01.11 Nivolumab Versus Placebo in Relapsed Malignant Mesothelioma: The CONFIRM Phase 3 Trial

Abstract: and PFS (RECIST v1.1; blinded, independent central review) were assessed by the stratified log-rank test in the ITT population. The protocol-specified first interim analysis (IA1) was planned to occur when w255 deaths occurred and w12 months after the last participant was randomized. Nonbinding futility criteria at IA1 were differences in the restricted mean survival time (RMST) between pembroeipi and pembroeplacebo of 0.2 at the maximum observation time and 0.1 at 24 months of follow-up. Results: Between 12-J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 0 publications
1
42
1
1
Order By: Relevance
“…In the NivoMes phase 2 study, a population of 38 patients with relapsed MPM was treated with nivolumab 3 mg/kg q14, obtaining a 3-month DCR of 50% and an ORR of 24%. The role of nivolumab as a salvage therapy was confirmed by the phase 2 MERIT trial and, most recently, by the phase 3 placebo-controlled CONFIRM trial: 332 patients were randomized 2:1 to nivolumab 240 mg q14 or placebo, stratified by histology (epithelioid vs. non epithelioid); the study met its two co-primary endpoints, showing an investigator-assessed mPFS of 3.0 vs. 1.8 months (HR 0.62, p < 0.001) and an investigator-assessed mOS of 9.2 vs. 6.6 months (HR 0.72, p = 0.02) in favor of nivolumab [ 25 , 26 , 27 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…In the NivoMes phase 2 study, a population of 38 patients with relapsed MPM was treated with nivolumab 3 mg/kg q14, obtaining a 3-month DCR of 50% and an ORR of 24%. The role of nivolumab as a salvage therapy was confirmed by the phase 2 MERIT trial and, most recently, by the phase 3 placebo-controlled CONFIRM trial: 332 patients were randomized 2:1 to nivolumab 240 mg q14 or placebo, stratified by histology (epithelioid vs. non epithelioid); the study met its two co-primary endpoints, showing an investigator-assessed mPFS of 3.0 vs. 1.8 months (HR 0.62, p < 0.001) and an investigator-assessed mOS of 9.2 vs. 6.6 months (HR 0.72, p = 0.02) in favor of nivolumab [ 25 , 26 , 27 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…Preliminary data from this study showed the safety of the treatment and proved that nivolumab improved both PFS rates at 12 months of treatment (14.5 in the nivolumab arm vs. 4.9 for placebo) and OS (9.2 months vs. 6.6). The significant clinical benefits were more evident for the epithelioid subtype [ 31 ].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…There was no statistically significant association between survival and PD-L1 status. 25 To prove, once more the importance of biomarker-based treatment selection, the randomized, phase III PROMISE-meso trial evaluated pembrolizumab versus standard chemotherapy in MPM patients. Patients were randomized (1:1) into two arms: one received pembrolizumab (200 mg i.v.…”
Section: M M U N Ot H E R a Pymentioning
confidence: 99%